Proposal of the Implementation of an International Pharmacy Graduate Preliminary Examination - Kyenghee Kwon; Jeoung Hill Park; Jinwoong Kim; Seung Ki Lee (Journal of Educational Evaluation for Health Professions, 2008)
At present, graduates of international pharmacy schools can apply to take the Korean Pharmacist Licensing Examination after passing a review by the Accreditation Board of the Pharmacy Schools and Licenses. However, since the educational content of different schools and the roles of pharmacists differ from country to country, a preliminary examination might be necessary before the Pharmacist Licensing Examination. To prepare to implement a preliminary examination for foreign pharmacy graduates in Korea, we summarized the preliminary examinations used in four other countries and presented a proposal for a preliminary examination. Data were collected via the internet and through telephone interviews with appropriate persons. The proposal was revised after a public forum. There are preliminary examinations in the USA, Canada, Australia, and the United Kingdom, and these involve written, oral, practice, and English proficiency tests. We proposed that the Korean preliminary examination consist of a written test on basic pharmacy, a test in the Korean language, and an interview. The preliminary examination should include suitable items that effectively evaluate international graduates. Graduates of international pharmacy schools who have an ability equivalent to graduates of Korean pharmacy schools should be eligible to write the Korean Licensing Examination.